Ironi dan Perjuangan Perempuan dalam Kajian Feminisme Puisi 'Manifesto' Karya Toeti Heraty - Nadhira, Yulia; Tanjung, Rezki Agus Pandai Yani; Akbar, Rizky Fauzan; Harahap, Muharrina; Wuriyani, Elly Prihasti (Universitas Islam Sumatera Utara, 2025)
The irony in women's struggle emerges when societal expectations clash with the reality of their pursuit of equality and freedom. Despite being confined by traditional gender roles, women persist in challenging patriarchal structures and reclaiming their rights. Toeti Heraty’s poem Manifesto eloquently captures this paradox, offering a powerful critique of patriarchy, gender stereotypes, and the systemic injustices faced by women. This study aims to examine the poem through the lens of feminist theory, highlighting the subversion of patriarchal norms and the position of women within the social hierarchy. Employing a qualitative descriptive method, the research analyzes the poetic devices and thematic elements used to convey feminist resistance. The findings indicate that Manifesto articulates the lived experiences of women under patriarchal oppression, underscores the ironic tension in the quest for emancipation, and ultimately calls for female agency in transforming a world shaped by male domination.